Binuclear Metal Chelates of 1,2,5,6-tetraphenyl-3,4-diaza- 1,6 Dihydroxyimino-2,4-hexadiene with Ni(II), Co(II), Mn(II) and Cu(II)
Binuclear metal chelates of 1,2,5,6-tetraphenyl-3,4-diaza-1,6-dihydroxyimino-2,4-hexadiene with Ni(II